Lanthanum and niobium doping on PZT ceramic synthesis - María D. Durruthy Rodríguez; Moisés Hernández García; Amaury Suárez Gómez (Revista CENIC Ciencias Químicas, 2002)
The effect of lanthanum and niobium doping on PZT piezoelectric ceramics was studied. Samples were prepared by burning (presintering) mixed metal oxides and carbonates at 1 233 K for 90 min and subsequent sintering at 1 523 K for 30, 60, 100, 150 and 300 min . The stoichiometric system Pb(Zr0.54 Ti0.46)O3 + x B [B = Nb2O5 or La2O3 , x = 0.6, 0.8, 1.0 (%wt)] was finally obtained. X Ray Diffraction and Optical Microscopy tests were carried out. As a result, the presinterized powder shows a distribution of narrow particle sizes (1 - 3 mm);all the compositions produce single-phase tetragonal samples. Grain size and porosity decrease as doping concentration increases. X Ray Diffraction shows important fiber textures appear in all the samples with [001] crystallite direction parallel to sample symmetry axes. Texture becomes more intense as the doping concentration increases and on niobium-doped  samples it is more intense than on the lanthanum-doped ones. The most suitable piezoelectric characteristics were obtained for 0.8 (%wt) [Nb] and 1.0 (%wt) [La] sintering during 100 min . It can be observed that electric losses decrease and electric permitivity increases as the doping concentration increases. The Curie point is 30 degrees below the reported value for a pure undoped PZT ceramic system.